2011
DOI: 10.1111/j.1365-313x.2011.04538.x
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the Arabidopsis glycerophosphodiester phosphodiesterase (GDPD) family reveals a role of the plastid‐localized AtGDPD1 in maintaining cellular phosphate homeostasis under phosphate starvation

Abstract: SUMMARYGlycerophosphodiester phosphodiesterase (GDPD), which hydrolyzes glycerophosphodiesters into snglycerol-3-phosphate (G-3-P) and the corresponding alcohols, plays an important role in various physiological processes in both prokaryotes and eukaryotes. However, little is known about the physiological significance of GDPD in plants. Here, we characterized the Arabidopsis GDPD family that can be classified into canonical GDPD (AtGDPD1-6) and GDPD-like (AtGDPDL1-7) subfamilies. In vitro analysis of enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
131
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(140 citation statements)
references
References 85 publications
9
131
0
Order By: Relevance
“…In response to a lack of Pi, we observed that NPC4, PLDz2, and GDPD1, 2, 3, 5, and 6 were induced in wild-type plants as previously reported (Supplemental Fig. 5; Nakamura et al, 2005;Li et al, 2006;Cheng et al, 2011), even if GDPD2 and 5 were only moderately induced. PLDz1 and PAH2 did not respond to Pi deficiency, and PAH1 was moderately (yet consistently) induced in the absence of Pi.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In response to a lack of Pi, we observed that NPC4, PLDz2, and GDPD1, 2, 3, 5, and 6 were induced in wild-type plants as previously reported (Supplemental Fig. 5; Nakamura et al, 2005;Li et al, 2006;Cheng et al, 2011), even if GDPD2 and 5 were only moderately induced. PLDz1 and PAH2 did not respond to Pi deficiency, and PAH1 was moderately (yet consistently) induced in the absence of Pi.…”
supporting
confidence: 89%
“…To verify if altered levels of PCho and PEth could lead to the transcriptomic activation or inhibition of specific lipid metabolism pathways, we selected several genes representative of membrane lipid recycling pathways triggered during Pi starvation (Nakamura, 2013). These genes included NPC4 (representative of the nonspecific PLC pathway; Nakamura et al, 2005), PLDz1 and 2, PAH1 and 2 (for the PLD/PAP pathway; Qin and Wang, 2002;Li et al, 2006;Nakamura et al, 2009;Eastmond et al, 2010), and GDPD1, 2, 3, 5, and 6 (for the LAH/GDPD pathway; Cheng et al, 2011). In response to a lack of Pi, we observed that NPC4, PLDz2, and GDPD1, 2, 3, 5, and 6 were induced in wild-type plants as previously reported (Supplemental Fig.…”
Section: Triple Ko Mutant Does Not Mimic or Amplify Phenotypes Causedmentioning
confidence: 99%
“…Of note, despite lacking the SPX domain, two glycerophosphodiester phosphodiesterases have recently been involved in maintaining cellular phosphate homeostasis in plants [63,64].…”
Section: Gde1 a Role In Scavenging Pimentioning
confidence: 99%
“…Lipid remodeling similar to that observed in P-limited Arabidopsis shoots (Kobayashi et al, 2009a) also occurred in H. prostrata leaves; galactolipids showed a negative correlation with Pi supply in all except senescing leaves, and phospholipids showed a positive correlation with Pi supply in all except young H. prostrata leaves. The decrease in galactolipid concentrations in young and mature leaves with Pi supply could be attributed to the P-dependent 4-to 5-fold decreases in transcripts encoding putative H. prostrata orthologs of the phosphodiesterase GDPD1 and the type B MGDG synthase MGD3 (Dubots et al, 2010;Cheng et al, 2011). The concomitant increase in phospholipids was accompanied by a modest 2-fold decrease in HpNPC4 and a 4-fold increase in HpNMT2 expression.…”
Section: The P Responsiveness Of Regulatory Network Is Reduced In Hmentioning
confidence: 94%
“…Alternatively, phospholipids can be deacylated by either phospholipase A in combination with lysophospholipase, phospholipase B, or lipid acyl hydrolase activities (Matos and Pham-Thi, 2009). GLYCEROPHOSPHODIESTER PHOSPHODI-ESTERASE (GDPD) subsequently hydrolyzes glycerophosphodiesters such as glycerophosphocholine into glycerol-3-phosphate and choline (Cheng et al, 2011).…”
mentioning
confidence: 99%